(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
This paper describes the validation of a reversed-phase high performance liquid chromatography method (RP-HPLC) with diode array detection (DAD) for determination of related substances (impurities from organic synthesis and degradation products) of captopril according to the Brazilian Pharmacopeia IV. The aim of this study was to guarantee the method accuracy for quantification of related substances, an essential requisite to determine, using the mass balance approach, the captopril content in the first Brazilian certified reference material (CRM) of an active pharmaceutical ingredient (API), developed by Inmetro. The captopril instability in solution is discussed and the captopril content determined by mass balance is compared to the results from titration and differential scanning calorimetry (DSC).